Examining Student Speaking Ability Through Zoom Application in Pandemic Covid-19 Era - Fahri Ali; Anita Rahmah Dewi (JELP Journal of English Language and Pedagogy, 2022)
This study aims to measure the effectiveness of the zoom application for junior high school students. This study uses experimental research with a pre-experimental design one-group pretest-posttest with a quantitative description of the method. The subjects of this study were 30 eighth grade students in semester 1. The Paired Sample t-test table showed that the average speaking score of the students on the pre-test and post-test increased from 43.70 to 55.47. This shows that the students' scores increased after being taught by using video blogs. The results of the paired sample t test also showed a sig value of .000. As a condition of the hypothesis, whether the significance value is less than the significance level (0.05), it means that the null hypothesis (Ho) is rejected while the alternative hypothesis (Ha) is accepted. From the above requirements it can be concluded that the null hypothesis (Ho) is rejected while the alternative hypothesis (Ho) is accepted. This means that there is a significant difference in students' speaking scores before and after being taught by using the zoom application as a media learning